Preoperative Deltoid Size and Fatty Infiltration of the Deltoid and Rotator Cuff Correlate to Outcomes After Reverse Total Shoulder Arthroplasty. Issue 2 (February 2015) - Wiater, Brett P.; Koueiter, Denise M.; Maerz, Tristan; Moravek, James E.; Yonan, Samuel; Marcantonio, David R.; Wiater, Michael J.
Abstract: Background: Reverse total shoulder arthroplasty (RTSA) allows the deltoid to substitute for the nonfunctioning rotator cuff. To date, it is unknown whether preoperative deltoid and rotator cuff parameters correlate with clinical outcomes. Questions/purposes: We asked whether associations exist between 2‐year postoperative results (ROM, strength, and outcomes scores) and preoperative (1) deltoid size; (2) fatty infiltration of the deltoid; and/or (3) fatty infiltration of the rotator cuff. Methods: A prospective RTSA registry was reviewed for patients with cuff tear arthropathy or massive rotator cuff tears, minimum 2‐year followup, and preoperative shoulder MRI. Final analysis included 30 patients (average age, 71 ± 10 years; eight males, 22 females). Only a small proportion of patients who received an RTSA at our center met inclusion and minimum followup requirements (30 of 222; 14%); however, these patients were found to be similar at baseline to the overall group of patients who underwent surgery in terms of age, gender, and preoperative outcomes scores. The cross‐sectional area of the anterior, middle, and posterior deltoid was measured on axial proton density‐weighted MRI. Fatty infiltration of the deltoid, supraspinatus, infraspinatus, teres minor, and subscapularis were quantitatively assessed on sagittal T1‐weighted MR images. Patients were followed for Constant‐Murley score, American Shoulder and Elbow Surgeons (ASES) scores, subjective shoulder value, pain, ROM, and strength. Correlations of muscle parameters with all outcomes measures were calculated. Results: Preoperative deltoid size correlated positively with postoperative Constant‐Murley score (67.27 ± 13.07) (ρ = 0.432, p = 0.017), ASES (82.64 ± 14.25) (ρ = 0.377; p = 0.40), subjective shoulder value (82.67 ± 17.89) (ρ = 0.427; p = 0.019), and strength (3.72 pounds ± 2.99 pounds) (ρ = 0.454; p = 0.015). Quantitative deltoid fatty infiltration (7.91% ± 4.32%) correlated with decreased postoperative ASES scores (ρ = −0.401; p = 0.047). Quantitative fatty infiltration of the infraspinatus (30.47% ± 15.01%) correlated with decreased postoperative external rotation (34.13° ± 16.80°) (ρ = −0.494; p = 0.037). Conclusions: Larger preoperative deltoid size correlates with improved validated outcomes scores, whereas fatty infiltration of the deltoid and infraspinatus may have deleterious effects on validated outcomes scores and ROM after RTSA. The current study is a preliminary exploration of this topic; future studies should include prospective enrollment and standardized MRI with a multivariate statistical approach. Quantitative information attained from preoperative imaging not only holds diagnostic value, but, should future studies confirm our findings, also might provide prognostic value. This information may prove beneficial in preoperative patient counseling and might aid preoperative and postoperative decision‐making by identifying subpopulations of patients who may benefit by therapy aimed at improving muscle properties. Level of Evidence: Level III, prognostic study.